Biological activity of glycine and alanine derivatives of quaternary ammonium salts (QASs) against micro‐organisms. (1st September 2019) - Rewak‐Soroczyńska, J.; Paluch, E.; Siebert, A.; Szałkiewicz, K.; Obłąk, E.
Abstract : Abstract: Quaternary ammonium salts (QASs) are commonly used in medicine, agriculture and industry and their wide usage caused the development of microbial resistance, thus there is still a need for new effective antimicrobial agents. Present work describes the biological activity of alanine‐ (DMALM‐n) and glycine‐derived (DMGM‐n) QASs against planktonic and biofilm forms of micro‐organisms. The antimicrobial activity was dependent mainly on the hydrocarbon chain length and surfactants with 12–16 atoms of carbon in the alkyl chain were the most active ones. The lowest MIC value was determined for DMALM‐14 against Rhodotorula rubra and Saccharomyces cerevisiae (2·5 µ mol l − 1 ). Generally, alanine derivatives showed stronger effects against micro‐organisms than glycine‐derived QASs. Alanine‐derived surfactants with 12–16 carbons in the alkyl chain had antiadhesive properties on the polystyrene surface, preventing cell attachment (about 70% of inhibition for C. albicans and 40% for S. epidermidis ). Strong adhesion reduction was also observed on the stainless steel surface and the highest reduction was observed for C. albicans cells incubated on surface pretreated with DMGM‐16. Moreover, DMGM‐16 and DMALM‐16 prevented C. albicans filamentation, one of the determinants of cell adhesion. Surfactants with C16 alkyl chain (DMGM‐16 and DMALM‐16) eradicated bacterial and yeast biofilm (from 60 to 90% of reduction observed after incubation of the previously grown biofilm in the presence of the highest tested concentration of the surfactant – 400 µ mol l − 1 ) and reduced its viability. Strong antimicrobial activity as well as antiadhesive properties make alanine‐ and glycine‐derived QASs the potential candidates for future application as disinfectants. Significance and Impact of the Study: Cationic surfactants are used in many fields, among others in medicine, cosmetic and pharmaceutical industry. Their usage on a large scale caused the development of microbial resistance mechanisms to such compounds. Thus, there is a need to synthesize new surfactants with potential application as effective disinfectants to combat both planktonic and biofilm forms of micro‐organisms. Present work focuses on the antimicrobial activity of chosen quaternary ammonium salts.